The role of immunohistochemistry for p16Ink4 in the diagnosis and management of squamous lesions of the cervix - Bezerra, João Victor da Silva; Lins, Armanda do Carmo Ponce de Leão; Eleutério, Renata Mirian Nunes (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Over the past few years, the role of the overexpression of the p16INK4a protein, as a substitute marker for high-risk human papillomavirus (hrHPV) associated with the cervix, has been well established(1). Missaoui et al.(2) demonstrated the role of overexpression of this protein as an additional useful marker for the interpretation of precancerous lesions during the evaluation of suspicious cervical biopsies. [...]